Evaluation of a non-domestic wastewater treatment system for the removal of organic cargo in the non-alcoholic beverage industry (2019)
The document presented here corresponds to the evaluation of a wastewater treatment system belonging to the manufacturing industry of carbonated and non-carbonated soft drinks. The development of this study was performed through 3 samplings carried out in the months of May, July and October (where the maintenance and cleaning operations of the system were carried out in July with the purpose of observing their implications in October) and 6 different points of the treatment plant were sampled. From the obtained samples, the insitu information was determined, the presence of bionutrients, the physical and chemical characteristics, and the BOD and COD parameters, in order to interpret their performance in terms of removal of contaminating organic load, and establish the control parameters required by the current legal regulations of the country to identify the problems existing in the system, their possible causes and the approach of a recommendation as a theoretical solution to the irregularities observed. It was evidenced that the pretreatment phase has a good performance in the development of treatment activities due to its stability in temperature and pH; however, the generation of residual sludge in this phase comprises a problem that directly impacts on the cost of operation and maintenance of the treatment system. The effluent from the production plant showed that the addition of chemical agents and the generation rate of activated sludge against the aerobic conditions of the system are the greatest support that the plant has to perform the processes of degradation in organic matter. The physicochemical characterization of the wastewater helped determine whether the mechanisms belonging to the treatment train developed their unit operations under efficient conditions for the reduction of organic load. Thanks to what was observed in this study, it would be beneficial for the system to implement complementary structures to the homogenizer tank and equalizer tank, for the reduction in the production of residual sludge, since this problem when being carried from the initial structures of the treatment train entails to the loss of efficiency in the subsequent processes to this throughout the system.